MicroRNA-98 Inhibits Hepatic Stellate Cell Activation and Attenuates Liver Fibrosis by Regulating HLF Expression - Wang, Qi; Wei, Song; Zhou, Haoming; Li, Lei; Zhou, Shun; Shi, Chengyu; Shi, Yong; Qiu, Jiannan; Lu, Ling (Frontiers in Cell and Developmental Biology, 2020)
Liver fibrosis is a major endpoint of patients with chronic liver diseases. The molecular mechanisms behind liver fibrosis remain largely unknown. Many studies have indicated the role of microRNA (miRNA) in hepatic tumorigenesis. But the role of miRNA in liver fibrosis is little known. Activated hepatic stellate cells (HSCs) can secret extracellular matrix proteins (ECM) and are the major contributors to liver fibrosis/cirrhosis. Here, microarray assay of quiescent and transforming growth factor β1 (TGF-β1) activated HSCs indicated that miR-98 might play a crucial role in liver fibrosis. We found that miR-98 was significantly downregulated in activated HSCs. miR-98 overexpression inhibited HSCs activation. Furthermore, we hypothesized that miR-98 regulated hepatic leukemia factor (HLF) expression by binding to the 3’UTR of its mRNA directly, as evidenced by luciferase reporter assay. HLF overexpression increased HSCs activation by inducing hypoxia inducible factor-1 alpha (HIF-1α) expression, resulting in the activation of TGF-β/Smad2/3 signaling pathway. Besides, low expression of miR-98 was also found in liver tissues from various fibrotic murine models, including carbon tetrachloride (CCl4), bile duct ligation (BDL), and high-fat diet (HFD)-induced liver fibrosis. miR-98 overexpression in vivo by ago-miR-98 injection could attenuate CCl4-, BDL-, and HFD-induced murine hepatic fibrosis. Meanwhile, miR-98 overexpression suppressed HLF expression and reduced fibrosis marker expression. Collectively, our study demonstrates that miR-98 suppress HSCs activation by targeting HLF directly and interacting with HIF-1α/TGF-β/Smad2/3 signaling pathway, which may be an effective therapeutic target for liver fibrosis.